Phytochemicals from Indian Medicinal Herbs in the Treatment of Neurodegenerative Disorders - Verma H.; Shivavedi N.; Nayak P.K. (My University, 2025)
Neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, Huntington's disease, and Amyotrophic lateral sclerosis are the major cause of disability and mortality. These disorders are appearing in the current era due to aging and stress-full lifestyles. For the treatments of these disorders, several conventional drugs are available but due to higher cost and dangerous adverse effects. Therefore, scientists are focusing more on medicinal herbs containing phytochemicals because these medicinal herbs are more effective, low cost, and show less harmful side effects to cure neurodegenerative disorders. Indian medicinal herbs are the most effective medicines and indigenous to India. Since ancient times, medicinal herbs have been used for treating neurodegenerative disorders. Indian medicinal herbs containing phytochemicals possess beneficial therapeutic effects for the treatment of neurodegenerative disorders, majorly having various compounds such as alkaloids, sesquiterpenes, triterpenoids, polyphenols, flavonoids, saponins, and essential oils which show anti-inflammatory and anti-oxidative properties. In this chapter, we highlighted and discussed the importance of some Indian medicinal herbs, such as Bacopa monnieri (Brahmi), Centella asiatica, Curcuma longa (turmeric), Allium sativum (garlic), Terminalia chebula (haritaki), Celastrus paniculatus (Jyotishmati), Glycyrrhiza glabra (Licorice), and Acorus calamus (Vacha) containing phytochemicals with their mechanism of action on neurodegenerative disorders. © 2022, Bentham Books imprint. All Rights Reserved.